Functional implication of ubiquitinating and deubiquitinating mechanisms in TDP-43 proteinopathies - Tran, Non-Nuoc; Lee, Byung-Hoon (Frontiers in Cell and Developmental Biology, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease in which motor neurons in spinal cord and motor cortex are progressively lost. About 15% cases of ALS also develop the frontotemporal dementia (FTD), in which the frontotemporal lobar degeneration (FTLD) occurs in the frontal and temporal lobes of the brain. Among the pathologic commonalities in ALS and FTD is ubiquitin-positive cytoplasmic aggregation of TDP-43 that may reflect both its loss-of-function and gain-of-toxicity from proteostasis impairment. Deep understanding of how protein quality control mechanisms regulate TDP-43 proteinopathies still remains elusive. Recently, a growing body of evidence indicates that ubiquitinating and deubiquitinating pathways are critically engaged in the fate decision of aberrant or pathological TDP-43 proteins. E3 ubiquitin ligases coupled with deubiquitinating enzymes may influence the TDP-43-associated proteotoxicity through diverse events, such as protein stability, translocation, and stress granule or inclusion formation. In this article, we recapitulate our current understanding of how ubiquitinating and deubiquitinating mechanisms can modulate TDP-43 protein quality and its pathogenic nature, thus shedding light on developing targeted therapies for ALS and FTD by harnessing protein degradation machinery.